Initial effects of the New York State auto safety belt law. - Latimer, E A (1987)
New York State began enforcing a mandatory automobile safety belt use law on January 1, 1985. We present a preliminary analysis of its effect on fatalities and injuries. Applying a Poisson statistical model to pre- and post-law belt usage rates together with counts of fatalities and injuries in 12 metropolitan areas, we estimate the first six months' application of the law averted 220 fatal, 1,500 severe, 4,600 moderate, and 2,600 light injuries across the state. The Poisson approach gives estimates of injuries averted considerably greater than simple year to year comparisons, indicating that media announcements have understated the efficacy of requiring safety belt usage.